Virulence genes and phylogenetic groups of uropathogenic Escherichia coli isolates from patients with urinary tract infection and uninfected control subjects: a case-control study - Rezatofighi, Seyedeh Elham; Mirzarazi, Mahsa; Salehi, Mansour (BMC infectious diseases, 2021)
Urinary Tract Infection (UTI) is one of the most common bacterial infectious diseases which causes considerable morbidity and costly health problems. Uropathogenic Escherichia coli (UPEC), the most common pathogen causing UTI, is a highly heterogeneous group of extraintestinal pathogenic E. coli (ExPEC) which may carry a variety of virulence factors and belonging to different phylogenetic backgrounds. The current study aimed to investigate the frequency and association between various virulence factors (VFs) and phylogenetic groups of UPEC and commensal isolates. UPEC and commensal E. coli strains isolated from UTI and feces of healthy humans were compared for the presence of VFs and phylogenetic groups. Association between virulence genes was investigated and cluster analysis was employed. According to the results, among a 30 virulence markers tested, the pathogenicity-associated island (PAI), papAH, papEF, fimH, fyuA, and traT genes prevalence were statistically significant in UPEC isolates. A strong association was found between the B2 and D phylogenetic groups and clinical isolates of UPEC; while, commensal isolates were mostly associated with phylogenetic group A. The aggregated VFs scores were more than twice higher in the UPEC isolates in comparison with the commensal isolates. Interestingly, the B2 group in both UPEC and commensal isolates had the highest VF scores. A strong positive association was found between several virulence genes. The clustering results demonstrated that UPEC or commensal E. coli isolates were highly heterogeneous due to different composition of their virulence gene pool and pathogenicity islands. Genetic structure and VFs of UPEC strains vary from region to region; therefore, to control the UTI, the epidemiological aspects and characterization of the UPEC isolates need to be investigated in different regions. Since UPEC isolates are generally originate from the commensal strains, it may be feasible to reduce the UTI burden by interfering the intestinal colonization, particularly in the highly pathogenic clonal lineages such as B2.